Social Support, Stressful Life Events, Medication-Taking Self-Efficacy, Psychotic Symptoms on Social Dysfunction: Role of Mediating Effects (Global Journal of Medical Research, 2018)
Abstract not found
Keywords: social support; medication taking selfefficacy; social dysfunction; path analysis